Welcome - Barroux 1965- (Egmont, 2016)
When Polar Bear and his friends are swept away from their icy home when the ice they are on melts. they hope to find refuge in a new land. But when they are turned away from one new place after another, they start to doubt that they will ever find somewhere they will be made welcome ... Barroux has crafted a powerful story with a twist ending about hugely important and current issues. A wonderful opportunity for parents to discuss with children the plight of migrants and refugees, as well as global warming, in a gentle, open-ended way
Keywords: Polar bear / Juvenile fiction; Refugees / Juvenile fiction; Emigration and immigration / Juvenile fiction; Picture books for children; Emigration and immigration; Polar bear; Refugees; Fiction; Children's picture books; Juvenile works; Picture books; Children's stories / Pictorial works; Bilderbuch